« Vous présentez mieux que vous ne parlez, chère collègue ! ». Genre et interruptions au Bundestag allemand (2013-2017) - Lucia Schmidt (Genre & Histoire)
Women have long been marginalized in the Bundestag and their situation remains precarious. From 1919, when they were granted the right to stand for election, until the 1980s, their presence hardly exceeded 10% and in the 18th legislature (2013-2017), their representation reached only 36%. Historically, this quantitative marginalization was accompanied by a strong resistance from their male counterparts, a phenomenon reflected at the linguistic level. Interruptions, which are traditionally more frequent during women’s speeches, are one such example. When tinged with a more or less acknowledged sexism, they aim to undermine the credibility of women’s speech, or even to confine them to their gender condition. The analysis of parliamentary debates of the 18th legislature (2013-2017) reveals that the situation is changing for the better, both in terms of the frequency and the content of interruptions. Nevertheless, although the interruptions are no longer overtly sexist and are more or less equally distributed between women and men, it appears that female MPs still tend to use a less confrontational communication style when interrupting others.